Farm visit L 19.-20.03.2020 (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2020)
157 JPEG files documenting participant observation on a farm in Southern Namibia
Keywords: Karakul sheep; Droughts; Agricultural laborers; Postcolonialism; South Africa; Agriculture; Colonisation; Namibia; Swakara; Karakul Circulations; Colonial Economies; Karakul Farming; Germany; Colonial South-West Africa; German Colonialism; Karakul Sheep Industry